(untitled) (American Journal of Islam and Society, 2002)
For many countries, the twentieth century was characterized by the shift from colonialism to independence. This struggle was contentious and often violent; the resulting governments frequently reflected the tensions between nationalist and colonial influences. In The Brunei Constitution of 1959: An Inside History, B. A. Hussainmiya examines the formation of the framework for the nonviolent and gradual movement toward independence through the negotiations surrounding the 1959 constitution. A historian, Hussainmiya’s previous works include his 1995 publication, Sultan Omar Ali Saifuddien III and Britain: The Making of Brunei Darussalam. The Brunei Constitution of 1959 began as a series of articles written for the Borneo Bul letin in 1999. This concise history of the 1959 Constitution is divided into eight chapters. The first two chapters provide background information, while chapters three to seven cover the negotiations between the British colonial government and Brunei’s monarchy. In chapter eight, the book ends with the constitution’s actual promulgation. Britain’s relationship with Brunei began in 1847, when the two countries signed a treaty of peace and friendship. In 1888 Britain established a protectorate over Brunei, which grew to residency rule by 1906. Although the establishment of residency rule in 1906 afforded the British vast and unspecified powers, a role for the Malay monarchy, through the sultan, was preserved and, in some respects, augmented. By designating, at least in theory, the sultan as the "absolute sovereign," the British hoped to maintain the perception that Brunei was not a colony. As Hussainmiya notes, the British also increased the sultan’s power over local nobles in an effort to increase their own power base ...